Reciprocal influence of B cells and tumor macro and microenvironments in the ApcMin/+ model of colorectal cancer. (3rd August 2017) - Mion, Francesca; Vetrano, Stefania; Tonon, Silvia; Valeri, Viviana; Piontini, Andrea; Burocchi, Alessia; Petti, Luciana; Frossi, Barbara; Gulino, Alessandro; Tripodo, Claudio; Colombo, Mario P.; Pucillo, Carlo E.
ABSTRACT: One of the most fascinating aspects of the immune system is its dynamism, meant as the ability to change and readapt according to the organism needs. Following an insult, we assist to the spontaneous organization of different immune cells which cooperate, locally and at distance, to build up an appropriate response. Throughout tumor progression, adaptations within the systemic tumor environment, or macroenvironment, result in the promotion of tumor growth, tumor invasion and metastasis to distal organs, but also to dramatic changes in the activity and composition of the immune system. In this work, we show the changes of the B-cell arm of the immune system following tumor progression in the Apc Min/+ model of colorectal cancer. Tumor macroenvironment leads to an increased proportion of total and IL-10-competent B cells in draining LNs while activates a differentiation route that leads to the expansion of IgA + lymphocytes in the spleen and peritoneum. Importantly, serum IgA levels were significantly higher in Apc Min/+ than Wt mice. The peculiar involvement of IgA response in the adenomatous transformation had correlates in the gut-mucosal compartment where IgA-positive elements increased from normal mucosa to areas of low grade dysplasia while decreasing upon overt carcinomatous transformation. Altogether, our findings provide a snapshot of the tumor education of B lymphocytes in the Apc Min/+ model of colorectal cancer. Understanding how tumor macroenvironment affects the differentiation, function and distribution of B lymphocytes is pivotal to the generation of specific therapies, targeted to switching B cells to an anti-, rather than pro-, tumoral phenotype.